2021
DOI: 10.12928/pharmaciana.v11i2.20674
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant-phenolic content correlation of phenolics rich fractions from Dillenia suffruticosa wood bark

Abstract: Dillenia suffruticosa is one of the tropical medicinal plants that has been used traditionally for treating several tropical diseases. However, phytochemical and pharmacological investigations of D. suffruticosa wood bark have not been well-investigated. This research aimed to investigate the correlation between antioxidant properties and total phenolic content of phenolics rich extract and fractions from D. suffruticosa wood bark. The phytochemical investigation revealed the existence of phenolics and alkaloi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
(6 reference statements)
0
1
0
2
Order By: Relevance
“…Based on qualitative testing, the three variants of kratom leaves show a change in concentrated green color, which is blackish green quickly after adding FeCl3 solution (Figure 5), so it is suspected that the third variant of kratom leaves has good antioxidant activity (Bayani, 2016). Muharini & Lestari (2021) found that there is a correlation between the content of phenolic compounds and the antioxidant activity of a plant. Setyawati (2020) showed that kratom leaves have antioxidant activity.…”
Section: Phenolic Screeningmentioning
confidence: 99%
“…Based on qualitative testing, the three variants of kratom leaves show a change in concentrated green color, which is blackish green quickly after adding FeCl3 solution (Figure 5), so it is suspected that the third variant of kratom leaves has good antioxidant activity (Bayani, 2016). Muharini & Lestari (2021) found that there is a correlation between the content of phenolic compounds and the antioxidant activity of a plant. Setyawati (2020) showed that kratom leaves have antioxidant activity.…”
Section: Phenolic Screeningmentioning
confidence: 99%
“…Penelitian terhadap bagian kayu batang simpur air berasal dari Kalimantan Barat, Indonesia yang menunjukkan adanya kandungan senyawa yaitu alkaloid, flavonoid, fenolik, saponin, steroid dan terpenoid. Analisis korelasi diketahui bahwa aktivitas antioksidan yang kuat dari ekstrak kayu batang simpur air disebabkan oleh kandungan fenoliknya (Muharini et al, 2021). Banyak penelitian telah mengungkapkan bahwa agen antioksidan ditemukan untuk menampilkan sifat farmakologis lain, seperti antiinflamasi (Chen et al, 2019), sitotoksisitas (Gacche & Jadhav, 2012) atau antikanker (Grigalius & Petrikaite, 2017).…”
Section: Pendahuluanunclassified
“…Penelitian terdahulu melaporkan bahwa kulit batang simpur air mengandung metabolit sekunder alkaloid, flavonoid, fenolik, saponin, steroid, dan terpenoid (Muharini et al, 2021). Senyawa yang diyakini berkontribusi terhadap sifat sitotoksik yang tinggi dari fraksi n-heksana merupakan senyawa yang bersifat non-polar, salah satunya adalah senyawa sterol yang merupakan subkelompok steroid.…”
Section: Pembahasan Sitotoksisitas Ekstrak Dan Fraksi Terhadap Sel Ka...unclassified